Design of Virtual Magnetic Dipole Antenna Array to Reduce the Systematic Bearing Error Caused by Wave Diffraction on the Antenna System and its Carrier Body - Ashikhmin, Alexandr V.; Ishchenko, Evgeniy A.; Pasternak, Yury G.; Pershin, Pavel V.; Sivash, Michail A.; Fedorov, Sergey M. (2020 7th All-Russian Microwave Conference (RMC), 2020)
the paper proposes a design of a vector antenna system that can be used for bearing radio emission sources with arbitrary polarization and an arbitrary wave incidence angle. The magnetic component of the field is used for bearing, since it is subject to less distortion. To calculate the magnetic field, the second Maxwell's equation in integral form is used. Based on the proposed field calculation method, a virtual antenna system that allows measuring magnetic field strength vectors using an antenna system consisting exclusively of electric dipoles, has been developed. The use of this method allows you to improve the bearing accuracy.